Application of the K-Means algorithm for clustering places to eat in Batubara - Kurniawan, Riski Askia; Hasibuan, Muhammad Siddik; Piramida, Piramida; Ramadhan, Rizky Syahrul (Journal of Computer Science and Informatics Engineering, 2022)
Batubara is a district that has a lot of tourism potential. Many tourist attractions make it possible to attract tourists to visit, besides considering tourist attractions, of course tourists glance at the culinary places served when visiting. Food stalls, restaurants and cafes in Batubara Regency are among them. We conducted research by collecting the number of places to eat (food stalls, restaurants, and cafes) in each sub-district in Batubara Regency in 2016, 2017, and 2021 and applying the K-Means Clustering algorithm, namely grouping the number of places to eat by year. The goal is for tourists to easily find culinary places and tourists also know where to eat based on the sub-districts that are in accordance with tourist attractions in Batubara Regency. The activity of collecting data on places to eat (food stalls, restaurants and cafes) is based on practical work activities held for 1 month by applying what was learned during lectures. Later the information obtained in this research is used to see the economic development and culinary places in Batubara Regency